Pt Single Atoms Loaded on Thin-Layer TiO2 Electrodes: Electrochemical and Photocatalytic Features - Zhou, Xin; Wang, Yue; Denisov, Nikita; Kim, Hyesung; Kim, Ji Hyeon; Will, Johannes; Spiecker, Erdmann; Vaskevich, Alexander; Schmuki, Patrik (Small, 2024)
Recently, the use of Pt in the form of single atoms (SA) has attracted considerable attention to promote the cathodic hydrogen production reaction from water in electrochemical or photocatalytic settings. First, produce suitable electrodes by Pt SA deposition on Direct current (DC)-sputter deposited titania (TiO2) layers on graphene—these electrodes allow to characterization of the electrochemical properties of Pt single atoms and their investigation in high-resolution HAADF-STEM. For Pt SAs loaded on TiO2, electrochemical H2 evolution shows only a very small overpotential. Concurrent with the onset of H2 evolution, agglomeration of the Pt SAs to clusters or nanoparticles (NPs) occurs. Potential cycling can be used to control SA agglomeration to variable-size NPs. The electrochemical activity of the electrode is directly related to the SA surface density (up to reaching the activity level of a plain Pt sheet). In contrast, for photocatalytic H2 generation already a minimum SA density is sufficient to reach control by photogenerated charge carriers. In electrochemical and photocatalytic approaches a typical TOF of ≈100–150 H2 molecules per second per site can be reached. Overall, the work illustrates a straightforward approach for reliable electrochemical and photoelectrochemical investigations of SAs and discusses the extraction of critical electrochemical factors of Pt SAs on titania electrodes.
CRIS-Team Scopus Importer:2024-08-23
Keywords: anatase thin film electrode; electrocatalytic hydrogen evolution; graphene; photocatalytic hydrogen evolution; Pt Single atom